PERAN FISIOTERAPI DALAM PENCEGAHAN CEDERA OVERUSE PADA PELARI MARATON - Marliana; Nurshal, Rezki Amalia; Muhammad (Journal of Hospital Administration and Management (JHAM), 2022)
Overuse injuries are common among marathon runners due to high training loads and repetitive movements. Physiotherapy plays a crucial role in preventing overuse injuries through rehabilitative and preventive approaches, including strength training, stretching techniques, and proper biomechanical education. This study aims to analyze the role of physiotherapy in preventing overuse injuries in marathon runners. This research adopts a qualitative descriptive design using in-depth interviews and observations with marathon runners undergoing preventive physiotherapy programs. The sample consists of professional and amateur marathon runners experiencing early symptoms of overuse injuries. Data were analyzed to identify the most effective physiotherapy interventions in reducing injury risks. The results indicate that physiotherapy programs incorporating core and lower limb strengthening exercises, dynamic stretching, and biomechanical correction techniques significantly reduce the risk of overuse injuries in marathon runners. Additionally, education on training load management and recovery contributes to long-term injury prevention. Therefore, physiotherapy should be an integral part of marathon runners' training programs to maintain optimal performance and prevent injuries.